Faktor Penyebab Perkelahian Carok di Madura di Tinjau Dari Kriminologi - Arif Rahman Hakim; Sulistyanta Sulistyanta (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research explores the phenomenon of carok as a form of traditional violence that persists in Madurese society, particularly in Sampang Regency. Carok refers to a duel involving sharp weapons, usually carried out by men to defend their honor and dignity, which they believe has been tarnished. This study aims to identify the factors that cause carok from a criminological perspective and to analyze the efforts that have been made to address and prevent such incidents. The research employs an empirical legal method with a qualitative approach. Data were collected through interviews with local police officers, sub-district officials, village heads, and traditional leaders in Sampang District, as well as through documentation and field observations. The findings reveal that the primary causes of carok include issues related to personal honor—especially concerning a man’s wife—personal disputes, revenge, and social environments that legitimize violence as a way of resolving conflict. From a criminological standpoint, carok can be explained through social conflict theory and the concept of crime of passion. Efforts to prevent carok have included both preventive measures, such as legal education, and repressive actions by law enforcement authorities. However, these efforts have proven to be only partially effective due to the deeply rooted cultural values that continue to support carok as a traditional form of justice. Therefore, a more intensive cultural approach involving community leaders is necessary to promote peaceful conflict resolution and reduce the incidence of violence.